Uji Aktivitas Sediaan Sampo Antiketombe Ekstrak Kulit Buah Naga (Hylocereus Polyrhizus) terhadap Pertumbuhan Jamur Candida Albicans Secara in Vitro - Zakiyatul Hamida; Panji Ratih Suci; Erna Fitriany; Cikra Ikhda Nur Hamidah Safitri; Nurfitriyawatie Nurfitriyawatie (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2024)
Dandruff is one of the problems that cause a lack of confidence. The triggering microorganism is Candida albicans. The innovation in the skin of red dragon fruit has the potential as an antibacterial and antifungal because it contains several active compounds such as alkaloids, terpenoids and flavonoids. This study aims to find out at what concentration the anti-dandruff activity on the growth of Candida albicans fungus in the formulation of dragon fruit peel extract shampoo preparation (Hylocereus polyrhizus). This research method is an experimental research using the disc paper diffusion method which consists of making dragon fruit peel extract with the maceration method using 96% ethanol solvent. The extract is formulated in shampoo with concentrations of 20.40 and 80%. The results of this study were in the organoleptis test in the form of a viscous liquid, soft sticky texture, brown and menthol flavor. pH test 6.13, 6.71, 6.39, 5.49. Test the height of the foam 5.8cm, 6.0cm, 6.5cm, 10.3cm. Viscosity test 500 Cp, 612 Cp, 635 Cp, 624 Cp. Homogeneity test is homogeneous. Anti-dandruff shampoo activity test of kontro (+), control (-), concentration of 20%, 40%, 80% with an average of 21.95 mm, 0.00 mm, 22.9 mm, 26.07 mm, 28.52 mm. The conclusion of this study is that the formulation of dragon fruit peel extract shampoo (Hylocereus polyrhizus) has provided an inhibitory effect on the growth of Candida albicans fungus with the strongest inhibitory concentration produced in formulation III with a concentration of 80% of 28.52 mm.